Polyadenylic acid sequences in rhinovirus RNA species from infected human diploid cells. - Macnaughton, M R (1975)
Polyadenylic acid sequences were shown to be present in rhinovirus virion RNA. Virus-specified RNA from human embryo lung cells infected with rhinovirus also contained polyadenylic acid but did not contain any polyuridylic acid sequences.